Characterization Of Halogen-Free Core Material With Various Flame Retardants - Wye Kheong, Patrick Lim (2012)
The effect of three different types of halogen-free flame retardants, which are the intumescent ammonium polyphosphates (APP), melamine cyanurate (MC) and calcium borate (CaB) on epoxy/glass fiber composites was studied. The single andhybrid flame retardant fillers were used to investigate the composites fire properties, mechanical and thermal properties. In general, after decompose at 700oC, CaB leaves behind the highest residual content, which mainly comprises of chars and glassy substrates. This is followed by APP which decomposes and forms the chars, while MC decomposes mainly into volatile gases. Among the three types, APP performed the best in flame retardancy while CaB is not effective in this composite. As for the mechanical properties of the composites, CaB gives the highest flexural strength while MC provides the highest flexural modulus to the composites. In terms of thermal properties, the flame retardants have lowered the thermal stability of the composites but did not significantly affect the coefficient of thermal expansion (CTE) and glass transition temperature (Tg). The second phase which studied on the hybrid system, found that APP-MC and APP-CaB according to 80-20 ratio gave synergistic effect on the fire properties to the composites. The hybrid compounds remain at Vhigher flexural strength, but was found not to affect the Tg and CTE. On the addition of 0.5 vol. % metal chelates into hybrid-flame retardant system, the fire resistance did not show any improvement in terms of their LOI values. The residual content of the flame retardants after decomposition have also decreased. The flexural properties, Tg and CTE were also not affected by the metal chelates